The short analytic proof of the friendly numbers problem, “THIS PAPER HAS BEEN WITHDRAWN” - Gilbert, Ikorong (International Journal of Advanced Mathematical Sciences, 2013)
“THIS PAPER HAS BEEN WITHDRAWN”